The Antibacterial Activity Test of Termas Stem Methanol Extract (Poikilospermum suaveolens (Blume) Merr.) Against Bacillus subtilis - nisa, anastia rahmatan (E-Jurnal Medika Udayana; Vol 14 No 2 (2025): E-Jurnal Medika UdayanaDO - 10.24843/MU.2025.V14.i2.P14, 2025)
Infectious diseases by pathogenic bacteria as Bacillus subtilis which have the ability of biofilms induced resistance of antibiotic. The development of alternative treatment needs to be supposed of them with natural ingredients. Termas ( Poikilospermum suaveolens (Blume) Merr.) has potential as an antibacterial agent containing flavonoid and phenolic compounds. The purpose of this study was to prove the antibacterial potential of Termas stem extract against Bacillus subtilis . The research design used was a post test only control group. The stem of Termas which have been determined at B2P2TOOT, Tawangmangu, were dried, sorted and extracted. The Termas stem extraction process used the soxhletation method at 40°C until the solvent was clear. Identification of compounds was carried out by spectrophotometry. The antibacterial activity test was carried out using the microdilution method to determine the minimum inhibitory concentration (MIC) and the scratch method to determine the minimum bactericidal concentration (MBC). The results showed the yield value of stem of Termas extract was 9.325% (maceration extract) and 17.665% (soxhletation extract). Identification of compound content by spectrophotometry showed that the total flavonoid content was 1.032 mgQE/g (0.0944%) and 42.397 mgQE/g (4.239%) and the total phenol content was 9.873 mgGAE/g (0.981%) respectively. and 88,390 mgGAE/g (8.839%). The antibacterial activity of the Termas stem extract was indicated by the MIC and MBC values ??of 40 mg/mL and 40 mg/mL respectively in the soxhletation extract and 80 mg/mL and 80 mg/mL in the maceration extract, respectively. Keywords:  The stem of Termas (Poikilospermum suaveolens (Blume) Merr.), MIC, MBC, Bacillus subtilis